Quilombos: the land is life and freedom - Amanda dos Santos Pereira (Pós)
Since Brazil's imperial era, the enslaved Black African population has sought ways to resist the horrors of slavery. Some of these groups were called quilombos, a word originating from the Bantu language, which means camp or fortress. This essay addresses the main dilemmas currently faced by Brazilian quilombos, such as the dispute over land, the fight against violence, and the violation of rights, as well as the study highlights the resistance processes created by these people to remain in the territory. This essay articulates some Afro-Brazilian intellectuals' thoughts as the discussions' main articulators. The theoretical framework of the study is based on the Afrodiasporic epistemic perspective. It is concluded that land and territory have a crucial meaning for the existence of quilombola communities, so it is urgent to implement public policies that recognize, respect, and guarantee the strengthening and preservation of quilombola communities in Brazil.